Vortex-induced Vibration of a Flexible Free-hanging Circular Cantilever - R. W. Prastianto; K. Otsuka; Y. Ikeda (Journal of Engineering and Technological Sciences, 2009)
The  behavior  of  a  free-hanging  riser  of  floating  offshore  structures would be different from  a  typical at-sea-floor-terminated riser type of oil or gas platforms.  For the design purpose, the present study  was intended to incorporate some  important  factors  of the riser conditions  (i.e.  bidirectional vibration,  freeend condition, and spanwise variation of response amplitude) for investigating its dynamics  characteristics.  An  experimental  investigation  on  time-dependent motion  of  a  flexible free-hanging circular cantilever  subjected to uniform crossflows has been carried out.  The  free-end condition  cantilever has  a  34.4  aspect ratio  and  a  low  mass ratio  of  about  1.24. The  cylinder  freely  oscillates in both inline  and  transverse  to  the  flow.  Reynolds  number  varied  from  10,800  to 37,800.  The "jump  phenomenon"  was found in the inline motion  of the cylinder that agrees well with an existing  comparable work.  At high flow velocities, the 3rd  higher  harmonic  frequencies  of  the  cylinder  transverse  response  became predominant that produce quite different motion  characteristics  compared to the other  existing  comparable  works  with  2-dimensional  bottom-end  condition. Generally, the results suggested that the flexible free-hanging cantilever generate different  vortex  wake  mode  than  either,  a  uniform  (a  short-rigid  flexiblymounted cylinder) or a linear amplitude variation along the span  case (a  pivoted cylinder)